Improved survival following ward-based non-invasive pressure support for severe hypoxia in a cohort of frail patients with COVID-19: retrospective analysis from a UK teaching hospital. Issue 1 (5th July 2020) - Burns, Graham P; Lane, Nicholas D; Tedd, Hilary M; Deutsch, Elizabeth; Douglas, Florence; West, Sophie D; Macfarlane, Jim G; Wiscombe, Sarah; Funston, Wendy
Abstract : Since the outbreak of COVID-19 in China in December 2019, a pandemic has rapidly developed on a scale that has overwhelmed health services in a number of countries. COVID-19 has the potential to lead to severe hypoxia; this is usually the cause of death if it occurs. In a substantial number of patients, adequate arterial oxygenation cannot be achieved with supplementary oxygen therapy alone. To date, there has been no clear guideline endorsement of ward-based non-invasive pressure support (NIPS) for severely hypoxic patients who are deemed unlikely to benefit from invasive ventilation. We established a ward-based NIPS service for COVID-19 PCR-positive patients, with severe hypoxia, and in whom escalation to critical care for invasive ventilation was not deemed appropriate. A retrospective analysis of survival in these patients was undertaken. Twenty-eight patients were included. Ward-based NIPS for severe hypoxia was associated with a 50% survival in this cohort. This compares favourably with Intensive Care National Audit and Research Centre survival data following invasive ventilation in a less frail, less comorbid and younger population. These results suggest that ward-based NIPS should be considered as a treatment option in an integrated escalation strategy in all units managing respiratory failure secondary to COVID-19.